2014
DOI: 10.1016/j.bjid.2013.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Cascade of access to interventions to prevent HIV mother to child transmission in the metropolitan area of Rio de Janeiro, Brazil

Abstract: Access to the full package of interventions for the prevention of HIV vertical transmission was low, with no significant trend of improvement over the years. The vertical transmission rates observed were higher than those found in reference services in the municipality of Rio de Janeiro and in the richest regions of the country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…The small number of cases resulted in an inaccurate estimate, varying from 0.3%-13.8%, and prevented the estimation of the MTCT by region in the country. However, these values are compatible with regional variation reported in local studies: rates of 2%-3% in studies conducted in the South [ 16 , 17 ], Southeast [ 7 , 8 , 18 20 ] and Midwest [ 21 , 22 ], and rates close to 10% in the North [ 10 ] and Northeast [ 9 ] regions of the country. The detection rate of cases of AIDS in children under 5 years old in the country follows this same pattern, with the Southeast, South and Midwest regions showing the biggest reduction trends; 73.2%.…”
Section: Discussionsupporting
confidence: 88%
“…The small number of cases resulted in an inaccurate estimate, varying from 0.3%-13.8%, and prevented the estimation of the MTCT by region in the country. However, these values are compatible with regional variation reported in local studies: rates of 2%-3% in studies conducted in the South [ 16 , 17 ], Southeast [ 7 , 8 , 18 20 ] and Midwest [ 21 , 22 ], and rates close to 10% in the North [ 10 ] and Northeast [ 9 ] regions of the country. The detection rate of cases of AIDS in children under 5 years old in the country follows this same pattern, with the Southeast, South and Midwest regions showing the biggest reduction trends; 73.2%.…”
Section: Discussionsupporting
confidence: 88%
“…In addition to the biological factors associated with an increased risk of MTCT, it is important to address several social factors that directly or indirectly hinder pregnant women's access to MTCT prevention services 28.…”
Section: Resultsmentioning
confidence: 99%
“…Research across various regions of Brazil has shown that lack of antenatal care and late diagnosis underlie substantial gaps in the PMTCT cascade [ 8 , 12 , 18 20 ]. In our cohort, while 19% of case and 29% of control mothers were not diagnosed prior to birth because they had not attended any or abandoned antenatal care, 25% of case and 14% of control mothers did not receive their diagnosis due to a failure in antenatal services—tests not being available, not ordered, or results not reported.…”
Section: Discussionmentioning
confidence: 99%
“…The Instituto Nacional de Saúde da Mulher, da Criança e do Adolescente Fernandes Figueira (IFF), located in the south zone of Rio de Janeiro, and the Hospital Federal dos Servidores do Estado (HFSE), located in the city centre, are tertiary hospitals that serve as the PMTCT reference centres for 58% of primary care units in Rio de Janeiro [ 11 ]. The Hospital Geral de Nova Iguaçu (HGNI) is located in a region of suburbs north of Rio de Janeiro called the Baixada Fluminense, and an estimated 12% of HIV-infected women in the state of Rio de Janeiro receive care at this hospital [ 12 ].…”
Section: Methodsmentioning
confidence: 99%